2016
DOI: 10.1155/2016/5670564
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection Outcomes for Gastroesophageal Tumors in Low Volume Units: A Multicenter Survey

Abstract: Background and Aims. Endoscopic submucosal dissection (ESD) outcomes have traditionally been reported from high volume centers in East Asia. Data from low volume centers in other parts of Asia remain sparse. Methods. A retrospective survey with a structured questionnaire of 5 tertiary centers in 3 countries in South East Asia was conducted. Details of training and clinical outcomes of ESD cases, with follow-up data from these centers, were analyzed. Results. Seven endoscopists from the 5 centers performed a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
4
1
Order By: Relevance
“…As mentioned earlier, our center had been performing ESD for several years prior to initiating our POEM service. The results of our ESD experience had been reported previously, 16 indicating a comparable outcome with large volume centers globally.…”
Section: A Multidisciplinary Expertise For Poemsupporting
confidence: 80%
See 1 more Smart Citation
“…As mentioned earlier, our center had been performing ESD for several years prior to initiating our POEM service. The results of our ESD experience had been reported previously, 16 indicating a comparable outcome with large volume centers globally.…”
Section: A Multidisciplinary Expertise For Poemsupporting
confidence: 80%
“…The incidence of gastric cancer is low in Malaysia and Southeast Asia 18 . Hence, the uptake and interest in ESD has been limited, apart from a few specialized centers 16 . In contrast, achalasia is not that uncommon 1 and hence relying solely on prior experience in ESD in this region will reduce the uptake of POEM in this region too.…”
Section: A Multidisciplinary Expertise For Poemmentioning
confidence: 99%
“…The technical indicators such as ESD time and en bloc resection rate were comparable with other studies. The details are presented in Table 3 and the comparison with other studies, which were conducted in areas with similar ESD development, is demonstrated in Table 4 22 23 24 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, unlike in Japan where young endoscopists can embark on ESD after adequate training, endoscopists in Southeast Asia accumulate significant amounts of endoscopic experience and perform endoscopic mucosal resections (EMR) prior to embarking on ESD. In the study conducted by Azmi et al, 7 all endoscopists had performed EMR previously before embarking on ESD, all endoscopists had completed animal model training for ESD, and three endoscopists underwent further training in Japan.…”
Section: Training Systems Around the Worldmentioning
confidence: 99%